M156. CORTICAL NEUROANATOMICAL SIGNATURE OF SCHIZOTYPY IN 2, 695 INDIVIDUALS ASSESSED IN A WORLDWIDE ENIGMA STUDY. (18th May 2020) - Antoniades, Mathilde; Nenadic, Igor; Kircher, Tilo; Krug, Alex; Meller, Tina; Grotegerd, Dominik; Fornito, Alex; Arnatkeviciute, Aurina; Dannlowski, Udo; DeRosse, Pamela; Moyett, Ashley; Baune, Bernhard; et al.
Abstract: Background: Cortical neuroanatomical abnormalities have been reported along a continuum between individuals with chronic schizophrenia, first-episode psychosis, clinical high risk for psychosis, and healthy individuals self-reporting subclinical psychotic-like experiences (or schizotypy). Recently, the Schizophrenia Working Group within the ENIGMA (Enhancing Neuro Imaging Genetics through Meta Analysis) consortium provided meta-analytic evidence for robust cortical thickness abnormalities in schizophrenia, while also indicating that these abnormalities are influenced by illness severity and treatment with antipsychotic medications. In this context, schizotypy research allows the investigation of cortical neuroanatomy associated with the expression of subclinical psychotic-like symptoms without the potential influence of a psychotic illness, its severity, or the use of antipsychotics. This study presents the first large-scale imaging meta-analysis of cortical thickness in schizotypy using standardized methods from 23 datasets worldwide. Methods: Cortical thickness and surface area were assessed in MRI scans of 2, 695 healthy individuals (mean [range] age of 29.1 [17–55.8], 46.3% male) who had also completed validated self-report schizotypy questionnaires. Each site processed their local T1-weighted MRI scans using FreeSurfer and, following the protocol outlined in the ENIGMA Schizophrenia Working Group study, extracted cortical thickness for 70 Desikan-Killiany (DK) atlas regions (34 regions per hemisphere + left and right hemisphere mean thickness). At each site, partial correlation analyses were performed between regional cortical thickness by ROI and total schizotypy scores in R, predicting the left, right and mean cortical thickness, adjusting for sex, age and site. Random-effects meta-analyses of partial correlation effect sizes for each of the DK atlas regions were performed using R's metafor package. False discovery rate (pFDR < .05) was used to control for multiple comparisons. Results: We found significant positive associations between subclinical psychotic-like experiences and mean cortical thickness of the medial orbitofrontal cortex (r = .077; pFDR = .006) and the frontal pole (r = .073; pFDR = .006). When assessed separately by hemisphere, meta-analysis revealed a significant positive association between subclinical psychotic-like experiences and cortical thickness of the left medial orbitofrontal cortex (r = .066; pFDR = .044), and at trend-level with the right medial orbitofrontal cortex (r = .062; pFDR = .053) and the left frontal pole (r = .062; pFDR = .053). No significant associations were observed for surface area. Discussion: Worldwide cooperative analyses of large-scale brain imaging data support a profile of cortical thickness abnormalities involving prefrontal cortical regions positively related to schizotypy in healthy individuals. These findings are not secondary to potential influences of disease chronicity or antipsychotic medication on the neuroanatomical correlates of psychotic-like experiences. The directionality of the observed meta-analytical effects in schizotypy is opposite to those previously reported in patients with schizophrenia (i.e., thinner cortex). The present findings of increased thickness may indicate early microstructural deficits (e.g. in myelination) that contribute to vulnerability for psychosis. Alternatively, these may reflect mechanisms of resilience associated with the expression of subclinical manifestations of psychotic symptoms in otherwise healthy individuals.